Patent landscape review of hydrogen production methods: Assessing technological updates and innovations - Arsad S.R.; Ker P.J.; Hannan M.A.; Tang S.G.H.; R S N.; Chau C.F.; Mahlia T.M.I. (Elsevier Ltd, 2025)
One of the keys to the implementation of hydrogen energy technology is the production of hydrogen. This review presents a comprehensive analysis of patents related to hydrogen production from the years 2013?2022. Using the Derwent World Patents Index (DWPI), the study includes bibliometric analysis, technology evaluation, and technology updates in the field of hydrogen production. The review focuses on the most recent patents related to hydrogen production and aims to identify the most promising methods for the efficient production of hydrogen. Special attention is given to innovations involving multiphase materials and novel electrocatalysts. The bibliometric analysis examines the patent landscape, identifies the top assignee, leading countries, and assesses patent trends in the field. Additionally, the review provides an overview of the various technologies used for hydrogen production and highlights the latest technology updates in hydrogen production, which include the new sources to produce hydrogen, the development of the device, the updated processing method, and the development of catalysts. Based on our analysis, China has emerged as the frontrunner in hydrogen patent publications, with the Huaneng Group being the top assignee. This review also highlighted on the factors contributing to China's prominent position in this field. Furthermore, the analysis of IPC codes reveals that electrolysis has emerged as the dominant method for hydrogen production, with a total of 611 patents published over a period of 10 years. Following closely behind is the decomposition of inorganic compounds, such as ammonia, employing diverse techniques like thermal decomposition and photolysis, with 464 patents granted over the same duration. This current patent review can be fully utilized by the researchers to keep abreast of the latest trends in hydrogen-generating strategies which could potentially aid in the development of innovative technologies and applications in the field. ? 2023 Hydrogen Energy Publications LLC